Value creation in selected Malaysian small and medium enterprises (SMEs) from activity, resource-based and dynamic capability perspectives / Mohd Bukhari Che Seman @ Sulaiman - Che Seman @ Sulaiman, Mohd Bukhari (Institute of Graduate Studies, UiTM, 2017)
Today, unlike in the 1970s and 1980s, for Malaysia, cheap labour is no longer a competitive advantage. Competitive and resilient SMEs are important in the growth and development process of the Malaysian economy including the adoption of appropriate strategies, as SMEs have great potential to be the engine of the economic growth as could be seen in other developed countries both in East and West like Germany and Japan (Khan and Khalique, 2014, pp. 40 – 41). With intense competition, firms are competing for resources to produce products and services demanded by the customers in the marketplace. In order to attract customers either to maintain or improve market shares, firms are forced to deliver the value added products and services which are better than their competitors. The term “value” as a concept is of interest to many disciplines including economics. Value in economics has been studied for more than 200 years and the concept is still evolving today. Thus, the adoption of strategic value creation approach is needed to steer the small and medium enterprises (SMEs) that contribute up to 90% of the economic activities of many countries in the world generally, and Malaysia particularly. This research aims to have an in-depth study on the value creating components and drivers from activity (value chain), resource-based and dynamic capability perspectives that affect performance of selected Malaysian SMEs. The case study approach adopts purposive sampling on SMEs involved in the food and beverage industry.